Analisis Pola Persebaran dan Jangkauan Fasilitas Pelayanan SMA, SMK, dan MA di Kabupaten Pacitan Tahun 2024 - Yannino Wisnu Suryo Sumirat; M Iqbal Taufiqurrahman Sunariya; Choirul Amin; Wahyu Tyas Pramono (Mataram University, 2026)
This study aims to analyze the distribution patterns, density levels, and coverage of educational facilities at the senior high school, vocational high school, and Islamic high school levels in Pacitan Regency in 2024. This study is motivated by the existing disparities in access to education and the phenomenon of several subdistricts in Pacitan being incorporated into the school zoning of Wonogiri Regency. This study employs a quantitative descriptive method utilizing Geographic Information Systems (GIS). Spatial analysis was conducted using the Average Nearest Neighbor (ANN) method to identify distribution patterns, Kernel Density for density analysis (hotspots), and the Buffer method with a radius of 3,000 meters in accordance with SNI 13-1733-2004 to measure service coverage. The ANN analysis results showed a nearest neighbor ratio of 0.773 with a z-score of -3.60, indicating that the distribution pattern of educational facilities tends to be clustered. The Kernel Density analysis revealed the highest concentration of schools in the districts of Pacitan, Tulakan, and Tegalombo, while outlying areas such as Donorojo have low density. Buffer analysis indicates that the coverage of public high schools (SMA, SMK, MA) currently covers only 44% of residential areas; however, when combined with private schools, coverage increases to 68%. There is an imbalance in the distribution of secondary education facilities in Pacitan Regency, which are concentrated in the central and southern areas. Although private schools greatly help expand access, the local government still needs to improve the equitable distribution of educational services in remote and border areas.